TEEG Induced A549 Cell Autophagy by Regulating the PI3K/AKT/mTOR Signaling Pathway - Lu Shi; Yijun Tu; Yu Xia; Siqi Ye; Chaozhi Ma; Yanwen Liu; Pengtao You (Analytical Cellular Pathology)
TEEG (3β,16β,23-trihydroxy-13,28-epoxyurs-11-ene-3-O-β-D-glucopyranoside) is derived from the chloroform extract of the Chinese medicine formula Shenqi San (CE-SS). In the present study, we aimed to elucidate the anticancer effect and possible molecular mechanism underlying the action of TEEG against the human non-small cell lung cancer (NSCLC) cell line A549 in vitro. A549 cells were incubated with different concentrations of TEEG. Cell proliferation was assessed by MTT assay. Autophagy was evaluated by immunofluorescence staining. Autophagy-associated proteins were examined by Western blot analysis. TEEG markedly inhibited A549 cell proliferation in a concentration-dependent manner. Immunofluorescence staining showed that TEEG induced autophagy in A549 cells. The LC3-II : LC3-I conversion ratio and the expression of Beclin-1, Atg5, Atg7, and Atg12 increased with the concentration of TEEG. In addition, increased TEEG concentration enhanced the expression of Class III p-PI3K and reduced the expression of Class I p-PI3K, p-AKT, p-mTOR, and p-P70S6K. These results indicate that TEEG induces autophagy of A549 cells through regulation of the PI3K/AKT/mTOR signaling pathway.